1985
DOI: 10.1590/s0071-12761985000200009
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de reguladores vegetais na germinação de sementes

Abstract: A aplicação de reguladores vegetais em sementes tem por objetivos quebrar a dormência e promover maior uniformidade no crescimento das plántulas. Com a finalidade de estabelecer os efeitos de alguns reguladores vegetais na germinação e desenvolvimento inicial de milho, crotalaria, lablab, amendoinzeiro, 'Kazungula', braquiaria, Stylosanthes, siratro, Tefrosia, soja perene e "green panic", sementes destas plantas foram imersas por 22 horas em soluções aquosas deCCC 2000 ppm, SADH 4000 ppm, GA 100 ppm, IAA 100 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…The levels and proportions of hormones in the composition of growth regulators influence the efficiency of these in the plant physiology, also as in carbon allocation (Castro and Vieira, 2001;Andrade et al, 2018), which may explain the influence only of the observed light radiation availability and production of biomass and essential oil. The ability to grow rapidly when shaded is a mechanism of acclimatization of the plants with a strategy to escape shading, can be attributed to a greater investment in cell elongation (Osunkoya and Ash, 1991;Moraes Neto et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The levels and proportions of hormones in the composition of growth regulators influence the efficiency of these in the plant physiology, also as in carbon allocation (Castro and Vieira, 2001;Andrade et al, 2018), which may explain the influence only of the observed light radiation availability and production of biomass and essential oil. The ability to grow rapidly when shaded is a mechanism of acclimatization of the plants with a strategy to escape shading, can be attributed to a greater investment in cell elongation (Osunkoya and Ash, 1991;Moraes Neto et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Durante o processo de germinação as auxinas estão envolvidas na permeabilidade das membranas e possuem relação direta com o crescimento de plântulas (CASTRO et al, 1985;CASTRO & VIEIRA, 2001;ROSS, 1992).…”
Section: (Recebido Em 21 De Setembro De 2006 E Aprovado Em 16 De Julhunclassified
“…As giberelinas também estimulam o alongamento e divisão celular e atuam também em conjunto com a auxina, promovendo maior crescimento do caule de certas plantas (CASTRO et al, 1985). Já as citocininas possuem grande capacidade de promover divisão celular, principalmente quando interagem com as auxinas.…”
Section: (Recebido Em 21 De Setembro De 2006 E Aprovado Em 16 De Julhunclassified